2017
DOI: 10.1007/s40846-017-0247-z
|View full text |Cite|
|
Sign up to set email alerts
|

Respiratory Rate Estimation by Using ECG, Impedance, and Motion Sensing in Smart Clothing

Abstract: The needs for light-weight and soft smart clothing in homecare have been rising since the past decade. Many smart textile sensors have been developed and applied to automatic physiological and user-centered environmental status recognition. In the present study, we propose wearable multi-sensor smart clothing for homecare monitoring based on an economic fabric electrode with high elasticity and low resistance. The wearable smart clothing integrated with heterogeneous sensors is capable to measure multiple huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 38 publications
2
44
0
Order By: Relevance
“…When a gyroscope was used in conjunction with a triaxial accelerometer on healthy subjects in stationary conditions, the average values of fR showed discrepancies always lower than 1.5 bpm (average error of 0.77 bpm), when compared to values manually counted by the authors [222]. Respiratory patterns obtained fusing accelerometer and gyroscope signals were investigated in [225]: the average error in estimating average fR values was 0.7 bpm during QB (max value of 2.0 bpm), and 3.0 bpm during running (max value of 4.0 bpm) [225].…”
Section: Techniques Based On Chest Wall Movement Analysismentioning
confidence: 99%
“…When a gyroscope was used in conjunction with a triaxial accelerometer on healthy subjects in stationary conditions, the average values of fR showed discrepancies always lower than 1.5 bpm (average error of 0.77 bpm), when compared to values manually counted by the authors [222]. Respiratory patterns obtained fusing accelerometer and gyroscope signals were investigated in [225]: the average error in estimating average fR values was 0.7 bpm during QB (max value of 2.0 bpm), and 3.0 bpm during running (max value of 4.0 bpm) [225].…”
Section: Techniques Based On Chest Wall Movement Analysismentioning
confidence: 99%
“…The traditional automatic measurement of RF is contact-based, which requires big devices such as the spirometry, capnotmetry, and impedance pneumography (Shen et al., 2017). In recent years, many innovative devices have been attempted to continuously measure RF in non-contact ways.…”
Section: Introductionmentioning
confidence: 99%
“…The ANOVA results showed that IJP sensor had high accuracy, good repeatability, and stability at different body postures. With no observable deviation from the reference sensor at all body postures, the accuracy of the IJP sensor was better than many sensors reported in the literature where the RR measured by stretchable sensor deviated from the reference value from 1.7% to more than 6% in different postures [4,12,[26][27][28][29][30].…”
Section: Ijp Sensor Accuracy: Comparison With Other Sensorsmentioning
confidence: 68%